The librarian's guide to micropublishing : helping patrons and communities use free and low-cost publishing tools to tell their stories - Crawford, Walt (Listen Alaska., 2012)
"In this timely book, Walt Crawford explains the how, what, and why of libraries and community micropublishing. He details the use of no-cost/low-cost publishing tools Lulu and CreateSpace and equips librarians to guide their patrons in the production of quality print books. He offers step-by-step instructions for using MS Word to design and edit manuscripts that can be printed in flexible quantities via on-demand technology. No stone goes unturned as Crawford demonstrates how, with a little attention to detail, anyone can produce books that rival the output of professional publishers. His advice is geared to making it easy for librarians to support local publishing without any additional budget, and libraries purchasing the book are granted permission to reproduce and supply key sections to their aspiring authors."--